The radiomorphological appearance of the invasive margin in pancreatic cancer is associated with tumor budding - Mayer, Philipp; Hausen, Anne; Wagner, Verena; Bergmann, Frank; Kauczor, Hans-Ulrich; Loos, Martin; Roth, Wilfried; Klauß, Miriam; Gaida, Matthias (Langenbeck's archives of surgery, 2024)
Pancreatic cancer (PDAC) is characterized by infiltrative, spiculated tumor growth into the surrounding non-neoplastic tissue. Clinically, its diagnosis is often established by magnetic resonance imaging (MRI). At the invasive margin, tumor buds can be detected by histology, an established marker associated with poor prognosis in different types of tumors.
Online veröffentlicht: 29. Mai 2024
Gesehen am 15.01.2025